Peace education : how we come to love and hate war - Noddings, Nel (Cambridge University Press, 2012)
"There is a huge volume of work on war and its causes, most of which treats its political and economic roots. In Peace Education: How We Come to Love and Hate War, Nel Noddings explores the psychological factors that support war: nationalism, hatred, delight in spectacles, masculinity, religious extremism and the search for existential meaning. She argues that while schools can do little to reduce the economic and political causes, they can do much to moderate the psychological factors that promote violence by helping students understand the forces that manipulate them"--Provided by publisher